2017
DOI: 10.1158/1078-0432.ccr-15-1823
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-Derived Suppressor Cell Subset Accumulation in Renal Cell Carcinoma Parenchyma Is Associated with Intratumoral Expression of IL1β, IL8, CXCL5, and Mip-1α

Abstract: Corresponding Author: C. Marcela Diaz-Montero, Ph.D., Department Immunology, Lerner Research Institute, Cleveland Clinic, 9500 Euclid Avenue, Cleveland, Ohio 44195. Conflict of interest: BR has received consulting fees from and performed contracted research for Bristol-Myers Squibb, GlaxoSmithKline, Merck, and Pfizer. Additionally, he has performed contracted research for Genentech. The remaining authors declare no conflict of interest. HHS Public Access Author Manuscript Author ManuscriptAuthor Manuscript Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
124
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 62 publications
0
124
1
Order By: Relevance
“…In contrast, our previous studies showed that the presence of a few PD‐1 + TILs was associated with the response to salvage chemotherapy, as well as nivolumab treatment . However, we did not clarify why preceding nivolumab therapy showed less antitumor activity in the responders to salvage chemotherapy.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In contrast, our previous studies showed that the presence of a few PD‐1 + TILs was associated with the response to salvage chemotherapy, as well as nivolumab treatment . However, we did not clarify why preceding nivolumab therapy showed less antitumor activity in the responders to salvage chemotherapy.…”
Section: Discussioncontrasting
confidence: 57%
“…Circulating MDSC levels were inversely associated with response rate and survival after treatment with nivolumab in cancer patients . In tumor‐bearing mouse models, the chemokine‐related substances that recruit neutrophils and MDSCs into the tumor suppressed the antitumor activity of PD‐1 blockade …”
Section: Discussionmentioning
confidence: 99%
“…The presence of granulocytes in the low‐density mononuclear fraction of peripheral blood in cancer patients has been previously reported in RCC, HNC, pancreatic cancer, colon cancer and breast adenocarcinoma patients…”
Section: Resultsmentioning
confidence: 64%
“…The presence of granulocytes in the low-density mononuclear fraction of peripheral blood in cancer patients has been previously reported in RCC, 29 HNC, 19 pancreatic cancer, colon cancer and breast adenocarcinoma patients. 18 We assessed the presence of LDN in lung cancer patients at early and advanced stages compared to COPD patients and healthy volunteers ( Table 1).…”
Section: Cd66b-positive Neutrophils Expand In the Low-density Pbmc mentioning
confidence: 60%
“…The mechanisms behind the tumor cell evasion include loss of tumor antigen expression, downregulation of human leukocyte antigens (HLA) from cancer cell surfaces, and recruitment of T‐regulatory cells (Tregs), myeloid derived suppressor cells, or tumor‐associated M2 macrophages, which all increase immunosuppression. These changes may lead to the upregulation of inhibitory receptors (e.g., cytotoxic T‐lymphocyte associated protein‐4 [CTLA‐4], PD‐1) on T cells, or of inhibitory ligands (e.g., PD‐L1) on tumor cells . Immunotherapies aim to counteract this escape phase and reinvigorate the patient's immune system to recognize and destroy cancerous cells.…”
Section: Introductionmentioning
confidence: 99%